Spatial Variability of pH and Organic Carbon in Soils under Bamboo Based Agroforestry Models in a Degraded Area - Behari, Bipin; Agarwal, Rashmi; Singh, A. K.; Banerjee, S. K. (Indian Forester, 2004)
Spatial variability of surface soil pH and organic carbon was studied in perpendicular transects at sites in near Jabalpur (M.P.) put to bamboo based agroforestry models and compared to control for two continuous years. The land under present study was degraded and occurs in a continuous path. Though, there was no systematic pattern of variation of values of pH and organic carbon in different directions, there was slightly less variability in North-South direction as compared to East-West direction. Overall, heterogeneity was found to be more in the first year than second year (i.e two seasons of agro-forestry land use). Shrubs and herbs invaded through bamboo based agroforestry practices in the degraded sites form the center of influence from which soil properties vary spatially.